Uncommon Complications of Ventriculoperitoneal Shunt Surgery: An Institutional Experience - Kumar, Ram Niranjan; Kanaujia, Niraj; Gupta, O.P.; Kumar, Brajesh; Singh, Samrendra Kumar (Journal of Neonatal Surgery, 2025)
Background:Ventriculoperitoneal (VP) shunt implantation continues to be the most commonly used surgical intervention for cerebrospinal fluid (CSF) diversion in the treatment of hydrocephalus. Although safe when performed as an individual operation, VP shunting is associated with a wide variety of complications ranging from frequent to rare occurrences. Rare complications, although not frequent, pose great diagnostic and therapeutic difficulties due to their variable and unpredictable manifestations. Because of their scarcity, very little literature and no standardized management guidelines exist to address these rare complications. Objective:The present study aims to analyze and share the institutional experiences in the identification, management, and outcomes of rare and atypical complications encountered following ventriculoperitoneal shunt surgeries. Methods:This retrospective case series includes six patients who developed uncommon complications following VP shunt procedures. All patients were managed at the Department of Neurosurgery, Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India for one year. Detailed clinical history, imaging findings, operative interventions, and outcomes were systematically analyzed to outline the clinical course of these unusual complications. Results:Complications noted out of the six patients were: proximal migration of the shunt into the lateral ventricle, formation of epidural and subdural hematomas, extrusion of the shunt through abdominal and retro auricular incisions, and cellulitis along the course of the shunt. Prompt diagnosis and proper surgical management in the form of revision of the shunt, evacuation of hematomas, and infection control resulted in a good outcome in all the cases. Most patients had a smooth postoperative recovery with minimal morbidity. Conclusion:With increasing utilization of ventriculoperitoneal shunt surgeries, uncommon complications are being reported more frequently. A high index of suspicion, prompt radiological evaluation, and timely intervention are essential to ensure optimal patient outcomes. Neurosurgeons should remain vigilant for such atypical presentations to reduce associated morbidity and mortality.